Against "Values": Reflections on Moral Language and Moral Education - Kenneth A. Strike (Arizona State University, 1993)
It is increasingly popular to ask educational institutions to do something about values. It is also becoming possible to take substantive moral positions in schools. We have become increasingly concerned about the morals of our children. Much of the discussion of values is incoherent. Many educators contribute to the public babble about ethics because of how they talk about moral questions; they have acquired a dysfunctional and obfuscating vocabulary ("values speak") for describing ethical phenomena and ethical issues. Assertions about values are distinct from assertions about character. The question of how to form democratic character is a crucial question that society has almost stopped asking. We do occasionally put the question as one about democratic values. While "values speak" seems initially liberating, nevertheless, it easily contributes to an authoritarian outlook. Four pieces of advice to educators are offered: 1) do not let "values speak" make you deaf to the nuances of the complex moral vocabularies; 2) learn to think of a liberal arts education as part of professional training; 3) an essential moral practice is dialogue; 4) support those trends in educational reform that increase opportunities for conscientious moral dialogue among members of school communities.